Networks, Agriculture and Geography: How business connections of agricultural enterprises shape the connection of settlements in Western Hungary - Szőke, Viktória; Kovács, László (Geographica Pannonica, 2023)
Networks and network science are not new: since the middle of the 20th century, networked structures are analyzed in geography. In recent years, however, with the emergence of network science, with the availability of big data, with improved computational capabilities and new software, the knowledge and analysis of networks have improved substantially. Present paper uses network science in economical geography: it analyzes the connections between settlements in western Hungary based on the business connections of agribusinesses. For the research, we used a questionnaire asking for purchase and sales connections of the selected agribusinesses and analyzed the results from the perspective of network science. Results show that in an agribusiness network the purchase network is more complex than the selling network and that in spatial networks connected to agribusinesses not large cities, but small towns and villages play a central role.